(untitled) (Journal of Informatics and Mathematical Sciences, 2016)
The first three Zagreb indices of a graph \(G\) denoted, \(M_1(G)\), \(M_2(G)\) and \(M_3(G)\), are well known. In this paper we derive recursive formula for these indices for the family of thorn Jaco graphs. The concept of a vertex invaded graph is also introduced.